Diagnostic errors in surgical pathology - Monique F. Santana; Luiz Carlos L. Ferreira (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Pathology must aim at a correct and complete diagnosis for the patient, timely, useful and understandable to the physician assistant. However, in daily practice, there are multiple possibilities of errors in the pathology laboratory, with several impacts on patient care and prognosis. In this review, we discuss the different concepts of error and diagnostic concordances in pathology, at which point in the diagnostic process the errors are more frequent, and propose solutions to minimize the chance of their occurrence.